1967
DOI: 10.1017/s0021859600018529
|View full text |Cite
|
Sign up to set email alerts
|

Potassium and caesium-137 distributions in Angus steer carcasses

Abstract: Seven Angus steers were reared under controlled conditions, slaughtered and their carcasses dissected. Muscles, fat, bones, connective tissues and samples of the steers' diet were measured by gamma spectrometry and the concentrations of potassium and caesium-137 determined. Significant variations in the concentration of each element were found both within and between tissues. Average potassium concentration was about four times greater in the muscle tissue than in the remainder of the carcass. Caesium/potassiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

1971
1971
2012
2012

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…Our results regarding the intermuscular distribution of radiocesium are in good agreement with previous studies of beef cattle 15,20) and reindeer. 18,19) In contrast, it has been reported that tongue, masseter, and diaphragm muscles showed higher radiocesium levels than other skeletal muscles in goats 30 min after 134 Cs administration.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…Our results regarding the intermuscular distribution of radiocesium are in good agreement with previous studies of beef cattle 15,20) and reindeer. 18,19) In contrast, it has been reported that tongue, masseter, and diaphragm muscles showed higher radiocesium levels than other skeletal muscles in goats 30 min after 134 Cs administration.…”
supporting
confidence: 93%
“…[6][7][8] Varying accumulation of radioisotopes among tissues in experimental and domestic animals has been found. [9][10][11][12][13][14][15] However, differences in radiocesium accumulation due to the nuclear accident among tissues in Japanese Black beef cattle have not been investigated under experimental control of feeding. This is the first study to demonstrate the distribution of radiocesium in tissues, including muscles of beef cattle fed roughage contaminated with radioactive fallout from the FDNPS accident by feeding experiment using roughage containing radiocesium at known concentrations.…”
mentioning
confidence: 99%
“…However, Duggleby and Seebeck [9] observed significant differences between some of the nine muscle groups of seven steers, and also Johnson et al [10] reported a variability of 137 Cs concentration of different wholesale cuts from five cows. Andersson and Hansson [11] found minor differences in 137 Cs concentration between seven muscles of lambs fed contaminated hay.…”
Section: Introductionmentioning
confidence: 96%
“…: [4][5][6][7][8][9][10]. From published values of transfer coefficients and biological half-lives, both the transfer of 137 Cs from feed to the body and excretion of 137 Cs can be considered to be very fast.…”
Section: Introductionmentioning
confidence: 99%